Characterization of the Weissert oceanic anoxic event in lower Cretaceous limestones of the Guaniguanico terrain, Sierra de los Órganos, Western Cuba - Orihuela, Johanset; Melinte Dobrinescu, Mihaela C.; Maurrasse, Florentin J.-M. R. (Frontiers in Earth Science, 2025)
The breakup of Pangea started in the Late Triassic when the new Tethyan domain developed into diverse sub-basins which began as shallow-water passive margins progressing into deeper foreland basins. Our study presents a high-resolution chemostratigraphic assessment of Lower Cretaceous organic-rich hemipelagic limestones from Sierra de los Órganos, Pinar del Río, Western Cuba, to assess the redox conditions in the Proto-Caribbean with respect to the dominant coeval global forcing factors in the Valanginian stage. To characterize presumed deoxygenation conditions associated with the Cuban deposit high-resolution lithostratigraphy, carbon geochemistry, trace element analysis, and biostratigraphy were performed on a ∼3-meter interval at the base of a 30-meter quarry outcrop located near the city of Pons. The succession consists of alternating thin grayish black (N2) chert-bearing carbonaceous marlstones and medium dark gray (N5) limestones. The carbonaceous marlstones yield a total inorganic carbon content (TIC) ranging from 44.7% to 77.3% and total organic carbon content (TOC) fluctuates between 3.5% and 10.82%. By contrast, the medium dark gray limestones have TIC values exceeding 90% and an average TOC of 2.3%. Petrographic analyses, radiography, and scanning electron microscopy imaging (SEM-EDS) revealed an isotropic fabric throughout the lighter micritic limestone, with a bioturbation index (BI) greater than 3, whereas the carbonaceous layers show BI consistently less than 2 and include single framboids and bundles of cubic pyrite. The carbon isotopic (δ13Corg) analysis gives an average value of approximately −27.3‰, with a main peak reaching around −25.56‰, corresponding to a ∼1.7‰ excursion. This carbon isotope excursion (CIE) correlates with the late Valanginian nannofossil subzone NK3B, as indicated by the presence of Calcicalathina oblongata and the disappearance of Rucinolithus wisei. The occurrence of calpionellids Tintinnopsella carpathica and Calpionellites cf. darderi supports the correlation up to the earliest Hauterivian. Enhanced values of redox-sensitive trace elements (V, Ni, Cr, Mo, TI, U, and S) correlative with highest TOC suggest severe deoxygenation conditions during the δ13Corg CIEs archived in this section. These excursions also coincide with increased enrichment of major elements (Al, Si, Li, and Ti), thus indicative of enhanced terrigenous fluxes at these intervals. The results provide robust evidence supporting the occurrence of distinct deoxygenation conditions in the deposits of Western Cuba originated from the Proto-Caribbean Seaway-Basin. They are coeval with the global Valanginian Weissert oceanic anoxic event. Thus, these results significantly enhance our comprehension of oxygen-deficient conditions as archived in this sub-basin and linked to the global event.